2022
DOI: 10.3390/vaccines10060890
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Anti-SARS-CoV-2 Total Antibodies and Spike Trimeric IgG after BNT162b2 Booster Immunization

Abstract: Objective: In this work we monitored both total and IgG anti-SARS-CoV-2 antibodies responses after BNT162b2 vaccine booster immunization in a cohort of ostensibly healthy healthcare workers. Methods: The study population consisted of 266 subjects (median age, 46 years and interquartile range (IQR), 35–52 years; 168 females) undergoing homologous 30-µg BNT162b2 booster administration. Serum samples were collected immediately before the booster dose and 1 month after. Results: The concentration of anti-SARS-CoV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…Nevertheless, these correlated to a lesser extent for sera from Unvac‐Ex ( ρ = 0.66) than those from Vac‐Ex ( ρ = 0.88) and Vac‐N ( ρ = 0.80), likely due to differences in the antigenic specificity of antibodies generated following vaccination or natural infection. In agreement with our findings, previous studies reported correlation levels between the Roche and DiaSorin immunoassays ranging from 0.80 to 0.93 in panels mostly comprising sera from vaccinated/naïve individuals 13–18 . The sizable difference between correlation levels across Vac‐Ex and Unvac‐Ex observed in our study are also congruent with findings by Lukaszuk et al 17 A relatively novel observation of this study relates to the impact of antibody concentration on the magnitude of quantitative discordances across the two immunoassays; in effect, for sera with <1000 BAU/ml, the DiaSorin assay returned higher values than the Roche assay, whereas the reverse was documented for sera ≥1000 BAU/ml.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, these correlated to a lesser extent for sera from Unvac‐Ex ( ρ = 0.66) than those from Vac‐Ex ( ρ = 0.88) and Vac‐N ( ρ = 0.80), likely due to differences in the antigenic specificity of antibodies generated following vaccination or natural infection. In agreement with our findings, previous studies reported correlation levels between the Roche and DiaSorin immunoassays ranging from 0.80 to 0.93 in panels mostly comprising sera from vaccinated/naïve individuals 13–18 . The sizable difference between correlation levels across Vac‐Ex and Unvac‐Ex observed in our study are also congruent with findings by Lukaszuk et al 17 A relatively novel observation of this study relates to the impact of antibody concentration on the magnitude of quantitative discordances across the two immunoassays; in effect, for sera with <1000 BAU/ml, the DiaSorin assay returned higher values than the Roche assay, whereas the reverse was documented for sera ≥1000 BAU/ml.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our findings, previous studies reported correlation levels between the Roche and DiaSorin immunoassays ranging from 0.80 to 0.93 in panels mostly comprising sera from vaccinated/naïve individuals. 13 , 14 , 15 , 16 , 17 , 18 The sizable difference between correlation levels across Vac‐Ex and Unvac‐Ex observed in our study are also congruent with findings by Lukaszuk et al 17 A relatively novel observation of this study relates to the impact of antibody concentration on the magnitude of quantitative discordances across the two immunoassays; in effect, for sera with <1000 BAU/ml, the DiaSorin assay returned higher values than the Roche assay, whereas the reverse was documented for sera ≥1000 BAU/ml. Although not explicitly stated, the occurrence of such differences in quantitative estimations of antibody levels provided by the Roche and DiaSorin immunoassays can be inferred from data from previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of a homologous BNT162b2 booster dose increased the VE to 58.9% (interquartile range [IQR] = 52.7%–63.3%) within 2–4 weeks. 7 , 30 , 32 , 33 , 34 This increase was consistent with the rise of binding (median fold increase = 26.8; IQR = 13.6–51.7) 35 , 36 , 37 and neutralizing antibodies (median fold increase = 27.3; IQR = 10.2–52.7). 18 , 19 , 38 , 39 , 40 , 41 However, a waning of protection against symptomatic diseases was rapidly observed 8–14 weeks after the booster (median VE = 37.9%; IQR = 24.6%–45.1%).…”
Section: Introductionsupporting
confidence: 79%